Investigations on the performance of bottle blade overshot water wheel in very low head resources for pico hydropower - Md Basar, Mohd Farriz; Akmal Zulkarnain, Izzatie; Sopian, Kamaruzzaman; Mohd Rais, Nurul Ashikin (Walter de Gruyter GmbH, 2024)
An overshot water wheel is considered as a low-cost and simple alternative for rural electrification. Hence, the aim of this study is to develop a noncomplex geometrical design of an overshot water wheel, namely, bottle blade overshot water wheel (BOWW), yet effectively operated for pico hydropower generation. The BOWW and hydro system were assessed at very low water head conditions, namely, 0.3, 0.4, and 0.5 m water head using a water test rig. According to the experimental results, the BOWW equipped with eight blades when operated at 0.5 m head produced significant mechanical power and electrical power up to 48.58 and 15.55 W. Analytically, the turbine with eight blades has 26.8–49.1% efficiency. Meanwhile, the effectiveness of four blades is between 5.66 and 28.96%. The results showed that eight blades performed well. Finally, it proves that, with a very low water head and low flow rate, the proposed system can perform and produce a significant power output for power generation.